Ecology and distribution of macroscopic algae communities in streams from the Basin of Mexico - Rogelio Rodríguez-Flores; Javier Carmona-Jiménez (Botan‪ical Sciences, 2018)
Background: Several studies of lotic ecosystems have provided important ecological information on the influence of environmental heterogeneity on macroscopic algae composition.